Marketing a Panic: Media Coverage of Novel Psychoactive Drugs (NPDs) and its Relationship with Legal Changes - Miller, Bryan Lee (American journal of criminal justice, 2015)
Recent social and legal responses to novel psychoactive drugs (NPDs) have been attributed to media panics rather than these substance’s actual harms. NPDs, including botanical substances new to Western markets such as Salvia divinorum , newly synthesized analogues such as synthetic cannabinoids and “bath salts,” and new ways of administering drugs, such as combining prescription cough syrup with soda (“purple drank”) have been the target of various forms of legislation at the state and/or federal level. We systematically examine print media coverage of NPDs in the U. S. between 2005 and 2013 to determine whether media attention was temporally associated with legislative change. Results indicate that each drug had a brief window during which it was the focus of sensationalistic reporting. In addition, federal legislation banning synthetic cannabinoids and “bath salts” appear to be closely linked to media reporting as spikes in coverage both preceded and followed the bans.